2018
DOI: 10.3889/oamjms.2018.220
|View full text |Cite
|
Sign up to set email alerts
|

Trend and Causes of Maternal Mortality in a Nigerian Tertiary Hospital: A 5-year Retrospective Study (2010-2014) at the University of Calabar Teaching Hospital, Calabar, Nigeria

Abstract: BACKGROUND:Maternal mortality ratios (MMR) are still unacceptably high in many low-income countries especially in sub-Saharan Africa. MMR had been reported to have improved from an initial 3,026 per 100,000 live births in 1999 to 941 in 2009, at the University of Calabar Teaching Hospital (UCTH), Calabar, a tertiary health facility in Nigeria. Post-partum haemorrhage and hypertensive diseases of pregnancy have been the common causes of maternal deaths in the facility.AIM:This study was aimed at determining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 23 publications
(33 reference statements)
2
22
2
Order By: Relevance
“…This is however lower than The Nigerian national MMR of 814 in 2015 recorded by WHO [1] and the 903.7 recorded by Nwagha et al [6] and much higher figures from other studies in Nigeria [17,18,19]. This is however higher than the findings of a similar study in the South-South region of Nigeria by Agan et al 2018 [15] of 448, but lower than their earlier finding of 1,513 at the same center in 2010 [8]. The success in reduction of MMR in their study was attributed to the free maternal care services to all categories of pregnant women in their state, as well as the Although the MMR of 644 in this study is lower than the current WHO estimate for Nigeria, it is abysmal when compared with the estimates for developed nations, such as 3 for Denmark, 8 for the UK, and 14 for Singapore [1].…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…This is however lower than The Nigerian national MMR of 814 in 2015 recorded by WHO [1] and the 903.7 recorded by Nwagha et al [6] and much higher figures from other studies in Nigeria [17,18,19]. This is however higher than the findings of a similar study in the South-South region of Nigeria by Agan et al 2018 [15] of 448, but lower than their earlier finding of 1,513 at the same center in 2010 [8]. The success in reduction of MMR in their study was attributed to the free maternal care services to all categories of pregnant women in their state, as well as the Although the MMR of 644 in this study is lower than the current WHO estimate for Nigeria, it is abysmal when compared with the estimates for developed nations, such as 3 for Denmark, 8 for the UK, and 14 for Singapore [1].…”
Section: Discussionmentioning
confidence: 60%
“…Nwagha et al [6] in their study also recorded consistent increase in the MMR over the 3-year period of 2003(756.8), 2004(897.6) and 2005(1052.2). However, Agan et al [15] reported a consistently decreasing MMR over their 5-year study period.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…At present, there are few studies in Nigeria reporting maternal deaths from pregnancies with an abortive outcome, and none is nationally representative . Likewise, institutional‐based reports on maternal near‐miss and deaths from ectopic pregnancy in the country are random and scarce .…”
Section: Introductionmentioning
confidence: 99%